2017
DOI: 10.1136/jnnp-2017-316631
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of intracerebral haemorrhage related to non-vitamin K antagonists oral anticoagulants versus vitamin K antagonists: a comprehensive systematic review and meta-analysis

Abstract: Our results confirm that ICH volume, haematoma expansion, mortality and functional outcome appear to be similar for NOAC-ICH versus VKA-ICH. Large prospective cohorts and updated meta-analyses are needed to provide more precise estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 34 publications
8
31
0
1
Order By: Relevance
“…12 A systematic review and meta-analysis of 12 studies published in 2018 including 393 NOAC-ICH and 3482 VKA-ICH reported similar results, 13 as did another recent prospective study including 62 NOAC-ICH and 134 VKA-ICH. 12 A systematic review and meta-analysis of 12 studies published in 2018 including 393 NOAC-ICH and 3482 VKA-ICH reported similar results, 13 as did another recent prospective study including 62 NOAC-ICH and 134 VKA-ICH.…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…12 A systematic review and meta-analysis of 12 studies published in 2018 including 393 NOAC-ICH and 3482 VKA-ICH reported similar results, 13 as did another recent prospective study including 62 NOAC-ICH and 134 VKA-ICH. 12 A systematic review and meta-analysis of 12 studies published in 2018 including 393 NOAC-ICH and 3482 VKA-ICH reported similar results, 13 as did another recent prospective study including 62 NOAC-ICH and 134 VKA-ICH.…”
mentioning
confidence: 67%
“…A recent international multicenter retrospective study found no difference in 3-month all-cause mortality or functional outcome between NOAC-ICH (n = 97) and VKA-ICH (n = 403). 12 A systematic review and meta-analysis of 12 studies published in 2018 including 393 NOAC-ICH and 3482 VKA-ICH reported similar results, 13 as did another recent prospective study including 62 NOAC-ICH and 134 VKA-ICH. 14 Tsivgoulis et al (Ann Neurol.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…We also consider that the results from the current IPDM, incorporating data from international multicenter cohorts, are likely to be more easily generalizable to every clinical setting. 37 The finding of lower baseline hematoma volumes in NOAC-ICH compared to VKA-ICH could be attributed to the more favorable pharmacological properties of NOACs, including shorter plasma half-life and selective inhibition of the extrinsic coagulation pathway, compared to VKAs. 36 A nonsignificant association for lower baseline ICH volume in NOAC-ICH compared to VKA-ICH was also reported in this meta-analysis (standardized mean difference = −0.24, 95% CI −0.52 to 0.04, p = 0.093), whereas the association of NOAC-related ICH with 30-day mortality was not evaluated in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%